2004
DOI: 10.1038/sj.jp.7211101
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Factors and Nontransfer of Small Babies: A Marker of Deregionalized Perinatal Care?

Abstract: OBJECTIVES:Our purpose was to examine the contribution of hospital factors (e.g., reimbursement sources, teaching status) to the rate of nontransfer of <1250 g infants born in nontertiary hospitals in Illinois. We chose nontransfer as a marker of the extent to which there have been structural changes in the regionalized perinatal care system in Illinois. STUDY DESIGN:Using data from live birth certificates (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996), from the American Hospital Association's Annual Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the only French study on this question, babies cared for in level IIB units had higher mortality regardless of gestational age 34 . A better understanding of the health consequences of these decisions and the factors which may make it possible to provide optimal care for high‐risk babies outside tertiary units is necessary as there is a growing trend in many countries towards a deregionalisation of perinatal care out of large tertiary centres 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…In the only French study on this question, babies cared for in level IIB units had higher mortality regardless of gestational age 34 . A better understanding of the health consequences of these decisions and the factors which may make it possible to provide optimal care for high‐risk babies outside tertiary units is necessary as there is a growing trend in many countries towards a deregionalisation of perinatal care out of large tertiary centres 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…Regionalisation was implemented in the late 1990s in France and some other countries of Europe and, in 2004, regionalised neonatal networks were established in the UK 1114. In the USA deregionalisation during the 1990s kept this issue on the research and policy agenda 15 16…”
Section: Introductionmentioning
confidence: 99%
“…12,24,25 Although a range of factors such as insurance status, maternal education, and obstetric risk factors can influence the choice of hospital for birth, increased availability of, and easier access to, midlevel units in some areas may have led to increased use. [26][27][28][29][30][31] The literature on the effects of NICU availability on use of different levels of care is sparse. Although recent studies have shown that more low birth weight (LBW) infants are being born and cared for at midlevel unit hospitals, none have specifically addressed how the entrance of a new midlevel NICU into an area affects where LBW infants are born in that area.…”
mentioning
confidence: 99%